A mediation model for relational aggression, victimization, attachment, and depressive symptoms in Guam: A gender-informed approach. (2020) - Kawabata, Yoshito; Nakamura, Monique S; De Luna, Mc Jason F
The present study examined the association between relational aggression and depressive symptoms, and the serial mediation of relational victimization and attachment insecurity in this association from a gender-informed approach. Participants consisted of 35 students (77% female; age: 18–25) for the pilot qualitative study and 206 students (68% female; age: 18–25) for the main quantitative study. Both sets of participants were recruited at the same public university in Guam. The qualitative data were transcribed verbatim and coded by three trained researchers (interrater agreement = 90%). From the qualitative data, several themes, such as relational aggression and victimization, physical aggression and victimization, negative affect and emotion, and culture emerged. All participants reported the use of relational aggression and showing negative emotions in a close relationship. Gender differences in the content of the themes were also found, such that relational aggression and victimization seemed to be more emotionally stressful for women than men. In line with these qualitative findings, the quantitative data showed that relational aggression was associated with depressive symptoms, and this association was mediated by relational victimization and attachment anxiety (not avoidance) only for women, while the contributions of physical aggression and victimization were controlled for. No direct and indirect links for physical aggression was evidenced. These findings are discussed from clinical, developmental and cultural perspectives.